2016
DOI: 10.1148/radiol.2015150947
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and Therapeutic Value of Human Adipose Tissue–derived Mesenchymal Stem Cell Transplantation in Reducing Venous Neointimal Hyperplasia Associated with Arteriovenous Fistula

Abstract: Purpose The purpose of this study was to determine if adventitial transplantation of human adipose derived mesenchymal stem cell (MSC) to the outflow vein of B6.Cg-Foxn1nu/J mice with AVF at the time of creation would reduce monocyte chemoattractant protein-1 (Mcp-1) gene expression and venous neointimal hyperplasia (VNH). The second aim was to track transplanted 89 zirconium (89Zr) labeled MSCs serially by positron emission tomography (PET) imaging for 21 days. Materials and Methods All animal experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…In arterial injury, the presence of local stem cells and circulating stem cells contributing to the pathologic process is very well recognized but the role of these cells in VNH is less well recognized [22, 23]. Finally, a recent study demonstrated that adventitial delivery of human adipose derived mesenchymal stem cells to the outflow vein of murine AVF reduces VNH mediated by a reduction in gene expression of Mcp-1 [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In arterial injury, the presence of local stem cells and circulating stem cells contributing to the pathologic process is very well recognized but the role of these cells in VNH is less well recognized [22, 23]. Finally, a recent study demonstrated that adventitial delivery of human adipose derived mesenchymal stem cells to the outflow vein of murine AVF reduces VNH mediated by a reduction in gene expression of Mcp-1 [24]. …”
Section: Discussionmentioning
confidence: 99%
“…These data show that the entire vessel wall is involved in the processes that lead to access failure, and suggest additional targets for potential therapy; recent studies have demonstrated the potential to target and treat the adventitial space to prevent the adventitial response to injury and prevent AVF failure [56, 144, 145]. …”
Section: Mechanisms Contributing To Avf Maturation and Failurementioning
confidence: 99%
“…An ongoing phase III randomized controlled trial is assessing the safety, efficacy, and patency outcomes of a perivascular sirolimus-eluting implant placed at the AVF anastomosis in hemodialysis patients receiving new AVFs (NCT02513303). Through the use of a similar concept, adipose-derived mesenchymal stem cells have been shown experimentally to reduce venous stenosis formation, and this technology is being proposed for use in a clinical trial (74). Finally, a small pilot study using adventitial delivery of calcitriol, a 1,25-dihydroxyvitamin D3 and inhibitor of Iex-1, at the time of angioplasty showed reduction in venous stenosis formation (75).…”
Section: Potential Future Molecular Targets That May Translate Into Tmentioning
confidence: 99%